2001
DOI: 10.1177/074193250102200602
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the 25th Anniversary of the Individuals with Disabilities Education Act

Abstract: November 29, 2000, marked the 25th anniversary of the signing into law of the Individuals with Disabilities Education Act (IDEA). This seminal law has improved the educational opportunities for students with disabilities in the United States. In this article we briefly review the IDEA's first 25 years and speculate on the direction the IDEA may take in the future. Our purpose in this article is to (a) present the litigative and legislative developments that led to the passage of IDEA, (b) examine the law itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 2 publications
0
43
0
Order By: Relevance
“…Remembering that special education is a highly litigious field (Katsiyannis et al, 2001), districts and agencies do well to ensure that personnel are not only qualified but are also appropriately trained.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remembering that special education is a highly litigious field (Katsiyannis et al, 2001), districts and agencies do well to ensure that personnel are not only qualified but are also appropriately trained.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…This is especially problematic in the field of special education where legal challenges abound. Katsiyannis, Yell, and Bradley (2001) indicated that, "perhaps no other area of educational law…has been more highly litigated than the education of students with disabilities" (p. 326).…”
Section: The Context Of Homebound Instructionmentioning
confidence: 99%
“…More recently, in 1997, the EHA was renamed the Individuals With Disabilities Education Act (IDEA), and federal funding was made available for early intervention services for infants, toddlers, and their families. IDEA also specifically identified ASDs as developmental disabilities and emphasized the importance of intervention for children with ASD (Katsiyannis et al, 2001). IDEA mandates the creation of an individualized family service plan (IFSP) for each infant or toddler diagnosed with a developmental problem of any kind, including ASD.…”
Section: Legislation Relating To Asdmentioning
confidence: 99%
“…The EHA authorized support both for expanded Head Start programs and for educational services for all children with disabilities. For the first time, every child age 3 to 21 in the United States, regardless of cognitive abilities, behavioral problems, or physical impairments, was guaranteed a free, appropriate public education (Katsiyannis, Yell, & Bradley, 2001).…”
Section: Legislation Relating To Asdmentioning
confidence: 99%
See 1 more Smart Citation